2008
DOI: 10.1097/npt.0b013e31818ee760
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Whole-Body Vibration on Lower Extremity Muscle Performance in Persons with Multiple Sclerosis

Abstract: Although not statistically significant, peak torque values for both quadriceps and hamstring muscles were consistently higher after 30 seconds of WBV at 26 vs 2 Hz. Whether WBV presents a viable treatment option as either a warm-up activity or a long-term exercise intervention is yet to be determined. Future studies should include a wider variety of WBV parameters and the use of functional outcome measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 23 publications
1
50
0
4
Order By: Relevance
“…Whole body vibration (WBV) is a novel rehabilitative exercise that uses low amplitude, low frequency vibration administered through a platform or Power Plate. WBV shows potential as an effective therapeutic approach and has been studied in a variety of clinical settings that include rehabilitation of patients with chronic stroke [8], spinal cord injury [9], lumbar disk disease and lower back pain syndromes [10], Parkinson's disease [11], elderly with sarcopenia [12,13], chronic obstructive pulmonary disease (COPD) [14 ], multiple sclerosis [15], obesity, osteoporosis, osteoarthritis and fibromyalgia [16] and children with cerebral palsy [17]. A growing body of evidence in laboratory animals and patients with chronic stroke have shown that WBV reduces or reverses pathological remodeling of bone and such a treatment could also help reduce frailty related physiological deterioration [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Whole body vibration (WBV) is a novel rehabilitative exercise that uses low amplitude, low frequency vibration administered through a platform or Power Plate. WBV shows potential as an effective therapeutic approach and has been studied in a variety of clinical settings that include rehabilitation of patients with chronic stroke [8], spinal cord injury [9], lumbar disk disease and lower back pain syndromes [10], Parkinson's disease [11], elderly with sarcopenia [12,13], chronic obstructive pulmonary disease (COPD) [14 ], multiple sclerosis [15], obesity, osteoporosis, osteoarthritis and fibromyalgia [16] and children with cerebral palsy [17]. A growing body of evidence in laboratory animals and patients with chronic stroke have shown that WBV reduces or reverses pathological remodeling of bone and such a treatment could also help reduce frailty related physiological deterioration [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of literature has reported benefit of WBV for patients with cystic fibrosis, [24] multiple sclerosis [25] and stroke [26]. To date, trials regarding efficacy of WBV in patients with COPD are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…The mean age of the groups ranged from 34 53 to 55 49,55 years. Participants were mostly females (range, 57%-100%) with RRMS and minimal to severe disability as measured using the EDSS.…”
Section: Vibration Interventionsmentioning
confidence: 99%
“…The most commonly excluded comorbidities were cardiovascular problems (eg, thrombosis and the use of pacemakers), 50,51,[53][54][55][56] epilepsy, 50,51,55,56 and psychiatric disorders 49,51,52 ( Figure 3). These psychiatric disorders were not identified.…”
Section: Vibration Interventionsmentioning
confidence: 99%
See 1 more Smart Citation